Multi-shell composite catalytic material as well as preparation method and application thereof
By using the multi-shell composite catalytic material Zn2MnO4/CdS, the problem of low efficiency of existing ZnO photocatalysts is solved, and efficient photocatalytic decomposition of water is achieved to produce hydrogen, and the material has good cycle stability.
Patent Information
- Application Number
- CN202411821811.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
Existing zinc oxide (ZnO) photocatalysts are inefficient when decomposing water to produce hydrogen, and can only absorb ultraviolet light, limiting their utilization efficiency of all light.
The multi-shell composite catalytic material Zn2MnO4/CdS is used, which is compounded by the transition bimetal oxide Zn2MnO4 and CdS to form a nano-multi-shell hollow spherical structure and nanoparticles, and is prepared by solvothermal method and hydrothermal method.
By increasing the specific surface area and providing more surfactant sites, the efficiency of photocatalytic decomposition of water to produce hydrogen is improved, efficient photocatalytic performance is achieved, and the circulation stability of the material is significantly improved.
Smart Images

Figure CN119633849A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation and application of inorganic functional composite materials, and relates to a multi-shell composite catalytic material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Zinc oxide (ZnO) is an n-type semiconductor with good photocatalytic activity. However, its bandgap is large (3.337 eV) and it can only absorb ultraviolet light, which limits its efficiency in utilizing all light. In addition, the conduction band potential of ZnO is lower than the potential for decomposing water to produce hydrogen. Therefore, the efficiency of using only ZnO as a photocatalytic water decomposition to produce hydrogen is extremely low. Although the combination of ZnO and CdS can significantly improve the efficiency of photocatalytic water decomposition to produce hydrogen, there is still a need for a photocatalyst with a higher efficiency for photocatalytic water decomposition to produce hydrogen. Summary of the invention
[0004] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a multi-shell composite catalytic material and its preparation method and application. The multi-shell structure of the Zn2MnO4 / CdS composite material provided by the present invention can provide a higher specific surface area and more surface active sites, thereby promoting photocatalytic decomposition of water to produce hydrogen. In addition, the transition bimetallic oxide Zn2MnO4 has multiple oxidation states, high electrochemical conductivity and high redox properties, so that it exhibits high catalytic activity, thereby achieving efficient photocatalytic performance.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In the first aspect, a multi-shell composite catalytic material is a composite material of transition bimetallic oxide Zn2MnO4 and CdS, wherein Zn2MnO4 is a nano multi-shell hollow sphere structure, CdS is a nanoparticle, and a plurality of CdS nanoparticles are coated on the surface of Zn2MnO4.
[0007] The Zn2MnO4 / CdS composite material with a multi-shell structure provided by the present invention has a special multi-shell hollow sphere structure, which can not only enhance the reflection and refraction of light and improve the light absorption capacity, but also increase the reaction active sites by increasing the specific surface area. In addition, the synergistic effect of different shells can provide a variety of reaction paths, thereby further improving the catalytic performance. At the same time, the heterojunction structure formed by Zn2MnO4 and CdS with an internal electric field can also promote the separation and migration of photogenerated carriers, and the transition bimetallic oxide Zn2MnO4 spinel structure has strong lattice stability and flexible metal ratio adjustment ability, which greatly improves the cyclic stability and durability of the material. The synergistic effect of the above characteristics makes the composite material show excellent photocatalytic activity.
[0008] In addition, if the Zn2MnO4 / CdS composite material does not have a multi-shell hollow sphere structure, the Zn2MnO4 / CdS photocatalyst with only a heterojunction has problems such as too fast electron-hole recombination rate and low visible light utilization rate. Therefore, the present invention sets the Zn2MnO4 / CdS composite material to a multi-shell hollow sphere structure, which can effectively improve the low visible light utilization rate.
[0009] It is worth noting that the present invention unexpectedly found through experiments that the Zn2MnO4 / CdS with a multi-shell structure provided by the present invention has a more significant photocatalytic hydrogen production activity than the Zn2MnO4 hollow sphere material with a multi-shell structure, which can reach 25.95mmol·g -1 ·h -1 class.
[0010] In a second aspect, a method for preparing the above-mentioned multi-shell composite catalytic material comprises the following steps:
[0011] The zinc salt, the manganese salt, the template agent and the chelating agent are uniformly mixed and then a bimetallic oxide precursor is prepared by a solvothermal method;
[0012] Calcining the bimetallic oxide precursor in an air atmosphere to obtain a Zn2MnO4 hollow sphere material with a multi-shell structure;
[0013] The Zn2MnO4 hollow sphere material with a multi-shell structure, cadmium salt and thioacetamide are dispersed in water and mixed evenly, and then subjected to a hydrothermal treatment to obtain the product.
[0014] The present invention has experimentally found that the Zn2MnO4 / CdS composite material obtained by performing the above treatment on the bimetallic oxide Zn2MnO4 hollow sphere material with a multi-shell structure can still maintain the unique multi-shell hollow structure, thereby obtaining a Zn2MnO4 / CdS composite material with a multi-shell structure.
[0015] In a third aspect, an application of the above-mentioned multi-shell composite catalytic material in photocatalytic water decomposition to produce hydrogen.
[0016] The beneficial effects of the present invention are:
[0017] The Zn2MnO4 / CdS composite material with a multi-shell structure prepared by the present invention first adopts a simple solvent thermal method to prepare a Zn2MnO4 hollow sphere material with a multi-shell structure, and then adopts a hydrothermal method to successfully obtain the Zn2MnO4 / CdS composite material by reacting Zn2MnO4 with a cadmium salt and thioacetamide. Compared with the physical mixing method commonly used in other composite materials, this method is more stable, can keep the original structure of the material intact, and at the same time improve the crystallinity of the composite material. During the reaction process, CdS nanoparticles are uniformly fixed on the inner and outer surfaces of Zn2MnO4 with a multi-shell structure by a hydrothermal method, forming a heterojunction with an internal electric field, thereby effectively separating and migrating photogenerated charges, inhibiting the recombination of photogenerated electron-hole pairs, and significantly improving the photocatalytic hydrogen evolution performance. In addition, the multi-shell hollow spherical structure of the Zn2MnO4 / CdS composite material with a multi-shell structure has clear internal voids, which provides more opportunities for multiple reflections and refractions of light, thereby enhancing the absorption and utilization efficiency of light. The structure also has abundant active sites and a large specific surface area, which is conducive to the adsorption of reactants. At the same time, Zn2MnO4, as a transition bimetallic oxide, has a high redox property, which enables it to exhibit excellent catalytic activity, thereby achieving efficient photocatalytic performance. It is worth noting that through the synergistic effect of the above characteristics, the photocatalytic activity of the Zn2MnO4 / CdS composite material with a multi-shell structure can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0019] Figure 1 The X-ray diffraction patterns (XRD) of the Zn2MnO4 hollow sphere material with a multi-shell structure, the granular CdS material and the Zn2MnO4 / CdS composite material with a multi-shell structure prepared in Examples 1, 2 and 5 of the present invention are shown.
[0020] Figure 2 This is a scanning electron microscope (SEM) of the Zn2MnO4 material with a multi-shell structure prepared in Example 1 of the present invention.
[0021] Figure 3 This is a transmission electron microscope (TEM) of the Zn2MnO4 material with a multi-shell structure prepared in Example 1 of the present invention.
[0022] Figure 4 This is a scanning electron microscope (SEM) of the Zn2MnO4 / CdS composite material with a multi-shell structure prepared in Example 5 of the present invention.
[0023] Figure 5 This is a transmission electron microscope (TEM) of the Zn2MnO4 / CdS composite material with a multi-shell structure prepared in Example 5 of the present invention.
[0024] Figure 6 It is a performance diagram of photocatalytic water decomposition and hydrogen production by Zn2MnO4 materials with multi-shell structures, granular CdS materials and Zn2MnO4 / CdS composite materials with multi-shell structures prepared in Examples 1, 2, 3, 4, 5, 6 and 7 of the present invention. DETAILED DESCRIPTION
[0025] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0026] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0027] Considering that the efficiency of photocatalytic water splitting to produce hydrogen by the composite of ZnO and CdS still needs to be improved, and the bimetallic peroxide Zn2MnO4 is relatively small, and the experiments of the present invention found that the hollow sphere material of Zn2MnO4 with a multi-shell structure has a low efficiency in photocatalytic water splitting to produce hydrogen, the present invention proposes a multi-shell composite catalytic material and its preparation method and application.
[0028] A typical embodiment of the present invention provides a multi-shell composite catalytic material, which is a composite material of transition bimetallic oxide Zn2MnO4 and CdS, wherein Zn2MnO4 is a nano multi-shell hollow sphere structure, CdS is a nanoparticle, and a plurality of CdS nanoparticles are coated on the surface of Zn2MnO4.
[0029] In some embodiments, the material has a multi-shell hollow structure in a transmission electron microscope (TEM) image. Specifically, the TEM image is as follows: Figure 5 shown.
[0030] Another embodiment of the present invention provides a method for preparing the above-mentioned multi-shell composite catalytic material, comprising the following steps:
[0031] The zinc salt, the manganese salt, the template agent and the chelating agent are uniformly mixed and then a bimetallic oxide precursor is prepared by a solvothermal method;
[0032] Calcining the bimetallic oxide precursor in an air atmosphere to obtain a Zn2MnO4 hollow sphere material with a multi-shell structure;
[0033] The Zn2MnO4 hollow sphere material with a multi-shell structure, cadmium salt and thioacetamide are dispersed in water and mixed evenly, and then subjected to a hydrothermal treatment to obtain the product.
[0034] The zinc salt described in the present invention refers to a compound whose cation is a zinc ion; it can be an inorganic salt, such as zinc chloride, zinc sulfate, zinc nitrate, etc.; it can also be an organic salt, such as zinc acetate. Studies have shown that the effect of using zinc acetate is better.
[0035] The manganese salt described in the present invention refers to a compound whose cation is a manganese ion; it can be an inorganic salt, such as manganese chloride, manganese sulfate, manganese nitrate, etc.; it can also be an organic salt, such as manganese acetate. Studies have shown that the effect of using manganese acetate is better.
[0036] In some embodiments, the template agent is polyvinyl pyrrolidone (PVP). The template agent of the present invention is polyvinyl pyrrolidone (PVP); it can be PVP with different average molecular weights (MW), such as 10000, 40000, 58000, 130000, etc. Studies have shown that polyvinyl pyrrolidone with an average molecular weight (MW) of 58000 has better effects.
[0037] The chelating agent described in the present invention is a compound that can form a stable chelate with metal zinc and manganese ions; it can be an inorganic chelating agent, such as sodium hexametaphosphate, sodium tripolyphosphate, boric acid, etc.; it can also be an organic chelating agent, such as salicylic acid. In some embodiments, the chelating agent is salicylic acid. Studies have shown that the effect of using salicylic acid is better.
[0038] The solvothermal method described in the present invention refers to a method of using an organic solvent or a non-aqueous solvent as a solvent, carrying out a reaction in a closed system (such as an autoclave), and creating a high-temperature and high-pressure environment by heating and pressurizing to perform a treatment.
[0039] In some embodiments, the zinc salt, manganese salt, template agent and chelating agent are calculated as zinc acetate dihydrate, manganese acetate tetrahydrate, PVP and salicylic acid, respectively, and the mass ratio of zinc salt, manganese salt, template agent and chelating agent is 0.4-0.6:0.2-0.3:1:0.3-0.5.
[0040] In some embodiments, the solvent used in the solvothermal method is ethanol.
[0041] In some embodiments, the temperature of the solvothermal method is 160-180° C., and the time is 10-12 h.
[0042] In some embodiments, the calcination temperature is 500-600°C, and the calcination time is 3.5-4.5 hours. Specifically, the calcination heating rate is 1-5°C·min -1 .
[0043] The cadmium salt described in the present invention refers to a compound whose cation is a cadmium ion; it can be an inorganic salt, such as cadmium chloride, cadmium sulfate, cadmium nitrate, etc.; it can also be an organic salt, such as cadmium acetate. Studies have shown that the effect of using cadmium acetate is better.
[0044] The hydrothermal method described in the present invention refers to a method of using water as a solvent, carrying out a reaction in a closed system (such as an autoclave), creating a high-temperature and high-pressure environment by heating and pressurizing, and thus performing a treatment.
[0045] In some embodiments, the temperature of the hydrothermal treatment is 180-190° C., and the time is 24-26 hours.
[0046] In some embodiments, the cadmium salt is calculated as cadmium acetate dihydrate, and the mass ratio of Zn2MnO4 hollow sphere material, cadmium salt and thioacetamide is 1:1.0-17.5:0.3-5.0. Studies have shown that the multi-shell composite catalytic material is related to the amount of cadmium salt and thioacetamide added. The cadmium salt is calculated as cadmium acetate dihydrate. When the mass ratio of Zn2MnO4 hollow sphere material, cadmium salt and thioacetamide is 1:3.70-3.80:1.20-1.30, the photocatalytic decomposition of water to produce hydrogen by the prepared multi-shell composite catalytic material is better.
[0047] A third embodiment of the present invention provides an application of the above-mentioned multi-shell composite catalytic material in photocatalytic water decomposition to produce hydrogen.
[0048] Specifically, the multi-shell composite catalytic material is added into a solution containing sodium sulfide and sodium sulfite, mixed evenly, and irradiated with light.
[0049] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0050] Embodiment 1:
[0051] A method for preparing a Zn2MnO4 hollow sphere material with a multi-shell structure comprises the following steps:
[0052] 1g PVP (average molecular weight 58000, K29-32, MW) was dissolved in 35mL ethanol solution, stirred at 360rpm for 15min at room temperature to dissolve it, then 0.5g zinc acetate dihydrate, 0.25g manganese acetate tetrahydrate and 0.4g salicylic acid were added, and magnetic stirring was performed at room temperature for 2h. The clear solution was transferred to a 50ml polytetrafluoroethylene-lined reactor and solvent thermally treated in an oven at 180℃ for 10h. After cooling naturally to room temperature, the obtained precipitate was centrifuged, washed, dried and ground, and the ground white powder was sintered in a tube furnace at 4℃·min -1 The temperature was raised to 600°C and calcined for 4 hours. After natural cooling and grinding, Zn2MnO4 hollow sphere material with a multi-shell structure was obtained.
[0053] Embodiment 2:
[0054] A method for preparing a granular CdS material comprises the following steps:
[0055] 7g of cadmium acetate dihydrate and 2g of thioacetamide were added to 30mL of deionized water, and then the mixture was ultrasonically treated for 15min and stirred continuously for 30min at room temperature to form a uniform suspension. The suspension was transferred to a 50ml polytetrafluoroethylene-lined reactor and hydrothermally treated in an oven at 180°C for 24h. After cooling naturally to room temperature, the precipitate was centrifuged, washed, dried, and ground to obtain a granular CdS composite material.
[0056] Embodiment 3:
[0057] A method for preparing a Zn2MnO4 / CdS composite material (denoted as ZMC-1) having a multi-shell structure comprises the following steps:
[0058] 0.4 g of the hollow Zn2MnO4 spheres with a multi-shell structure prepared in Example 1 were added to 30 mL of deionized water, and then the mixture was ultrasonically treated for 15 min and stirred continuously at room temperature for 30 min. Then, 7 g of cadmium acetate dihydrate and 2 g of thioacetamide were added, and the mixture was stirred continuously at room temperature to form a uniform suspension. The obtained suspension was transferred to a 50 ml polytetrafluoroethylene-lined reactor and hydrothermally treated in an oven at 180° C. for 24 h. After cooling naturally to room temperature, the obtained precipitate was centrifuged, washed, dried, and ground to obtain a Zn2MnO4 / CdS composite material with a multi-shell structure.
[0059] Embodiment 4:
[0060] A method for preparing a Zn2MnO4 / CdS composite material (denoted as ZMC-2) having a multi-shell structure comprises the following steps:
[0061] 0.4 g of the hollow Zn2MnO4 spheres with a multi-shell structure prepared in Example 1 were added to 30 mL of deionized water, and then the mixture was ultrasonically treated for 15 min and stirred continuously at room temperature for 30 min. Then, 3 g of cadmium acetate dihydrate and 1 g of thioacetamide were added, and the mixture was stirred continuously at room temperature to form a uniform suspension. The obtained suspension was transferred to a 50 ml polytetrafluoroethylene-lined reactor and hydrothermally treated in an oven at 180° C. for 24 h. After cooling naturally to room temperature, the obtained precipitate was centrifuged, washed, dried, and ground to obtain a Zn2MnO4 / CdS composite material with a multi-shell structure.
[0062] Embodiment 5:
[0063] A method for preparing a Zn2MnO4 / CdS composite material (denoted as ZMC-3) having a multi-shell structure comprises the following steps:
[0064] 0.4 g of the hollow Zn2MnO4 spheres with a multi-shell structure prepared in Example 1 were added to 30 mL of deionized water, and then the mixture was ultrasonically treated for 15 min and stirred continuously at room temperature for 30 min. Then, 1.5 g of cadmium acetate dihydrate and 0.5 g of thioacetamide were added, and the mixture was stirred continuously at room temperature to form a uniform suspension. The obtained suspension was transferred to a 50 ml polytetrafluoroethylene-lined reactor and hydrothermally treated in an oven at 180° C. for 24 h. After cooling naturally to room temperature, the obtained precipitate was centrifuged, washed, dried, and ground to obtain a Zn2MnO4 / CdS composite material with a multi-shell structure.
[0065] Embodiment 6:
[0066] A method for preparing a Zn2MnO4 / CdS composite material (denoted as ZMC-4) having a multi-shell structure comprises the following steps:
[0067] 0.4 g of the hollow Zn2MnO4 spheres with a multi-shell structure prepared in Example 1 were added to 30 mL of deionized water, and then the mixture was ultrasonically treated for 15 min and stirred continuously at room temperature for 30 min. Then, 0.75 g of cadmium acetate dihydrate and 0.25 g of thioacetamide were added, and the mixture was stirred continuously at room temperature to form a uniform suspension. The obtained suspension was transferred to a 50 ml polytetrafluoroethylene-lined reactor and hydrothermally treated in an oven at 180° C. for 24 h. After cooling naturally to room temperature, the obtained precipitate was centrifuged, washed, dried, and ground to obtain a Zn2MnO4 / CdS composite material with a multi-shell structure.
[0068] Embodiment 7:
[0069] A method for preparing a Zn2MnO4 / CdS composite material (denoted as ZMC-5) having a multi-shell structure comprises the following steps:
[0070] 0.4 g of the hollow Zn2MnO4 spheres with a multi-shell structure prepared in Example 1 were added to 30 mL of deionized water, and then the mixture was ultrasonically treated for 15 min and stirred continuously at room temperature for 30 min. Then, 0.4 g of cadmium acetate dihydrate and 0.125 g of thioacetamide were added, and the mixture was stirred continuously at room temperature to form a uniform suspension. The obtained suspension was transferred to a 50 ml polytetrafluoroethylene-lined reactor and hydrothermally treated in an oven at 180° C. for 24 h. After cooling naturally to room temperature, the obtained precipitate was centrifuged, washed, dried, and ground to obtain a Zn2MnO4 / CdS composite material with a multi-shell structure.
[0071] See Figure 1 The XRD spectra of Zn2MnO4, CdS and the Zn2MnO4 / CdS composite material with a multi-shell structure prepared by the present invention show the characteristic peak of Zn2MnO4, proving that Zn2MnO4 is successfully prepared. At the same time, the characteristic peak of CdS is also shown in the figure, proving that CdS is successfully prepared. The characteristic peaks attributable to Zn2MnO4 and CdS are shown in the XRD graph of the Zn2MnO4 / CdS composite material, and the peak intensity of Zn2MnO4 gradually decreases with the increase of CdS content, while the peak intensity of CdS gradually increases with the increase of CdS content, which also shows that the Zn2MnO4 / CdS composite material with a multi-shell structure is successfully prepared.
[0072] See Figure 2 From the SEM image of the Zn2MnO4 hollow sphere with a multi-shell structure prepared in the present invention, it can be seen that the Zn2MnO4 material has a spherical morphology.
[0073] See Figure 3 The TEM image of the Zn2MnO4 hollow sphere with a multi-shell structure prepared in the present invention shows that the Zn2MnO4 material has a multi-shell hollow structure.
[0074] See Figure 4 From the SEM image of the Zn2MnO4 / CdS composite material with a multi-shell structure prepared in the present invention, it can be seen that the Zn2MnO4 / CdS composite material has a spherical morphology.
[0075] See Figure 5 From the TEM image of the Zn2MnO4 / CdS composite material with a multi-shell structure (denoted as ZMC-3) prepared by the present invention, it can be seen that the composite material still maintains a multi-shell hollow sphere structure, indicating that the Zn2MnO4 / CdS composite material prepared by coating CdS does not break the original multi-shell hollow structure.
[0076] The obtained Zn2MnO4 / CdS composite material with a multi-shell structure was applied to photocatalytic water decomposition to produce hydrogen, and the experimental process is as follows:
[0077] 10 mg of the photocatalyst prepared in Examples 1, 2, 3, 4, 5, 6, and 7 of the present invention was added to 90 mL of a mixed solution of 0.35 M sodium sulfide nonahydrate and 0.25 M sodium sulfite and ultrasonically dispersed uniformly. The suspension was transferred into a reactor, and the reactor was irradiated with a 300 W xenon lamp as simulated sunlight. The amount of hydrogen generated was detected using an online gas chromatograph equipped with a thermal conductivity detector, and the hydrogen production efficiency of the photocatalyst was further calculated in combination with a pre-drawn standard curve.
[0078] The efficiency of photocatalysts for decomposing water to produce hydrogen in various embodiments of the present invention is shown in Figure 6 ,from Figure 6 It can be seen that the prepared Zn2MnO4 / CdS composite material with a multi-shell structure and the photocatalytic water decomposition hydrogen production efficiency are higher than those of the Zn2MnO4 hollow sphere material with a multi-shell structure, especially the ZMC-3 prepared in Example 5, whose photocatalytic water decomposition hydrogen production efficiency reaches 25.95mmol·g -1 ·h -1 , which is about 13 times that of the Zn2MnO4 hollow sphere with a multi-shell structure. The construction of the multi-shell hollow structure and the formation of a heterojunction with an internal electric field improve the efficiency of the composite material in photocatalytic hydrogen production. This may be because the presence of the multi-shell structure gives it a larger surface area and higher light collection efficiency, which can greatly increase the reaction active sites and enhance the utilization of light. At the same time, the construction of a heterojunction with an internal electric field can effectively inhibit the recombination of photogenerated carriers, so that the composite material exhibits excellent photocatalytic activity and achieves efficient hydrogen evolution activity. The above results show that the construction of a multi-shell structure and the formation of a heterojunction are of great significance for improving the photocatalytic activity of the composite material.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A multi-shell composite catalytic material, characterized in that it is The composite material of transition bimetallic oxide Zn2MnO4 and CdS, Zn2MnO4 is a nano multi-shell hollow sphere structure, CdS is a nanoparticle, and a plurality of CdS nanoparticles are coated on the surface of Zn2MnO4.
2. A method for preparing the multi-shell composite catalytic material according to claim 1, characterized in that: The steps include: The zinc salt, the manganese salt, the template agent and the chelating agent are uniformly mixed and then a bimetallic oxide precursor is prepared by a solvothermal method; Calcining the bimetallic oxide precursor in an air atmosphere to obtain a Zn2MnO4 hollow sphere material with a multi-shell structure; The Zn2MnO4 hollow sphere material with a multi-shell structure, cadmium salt and thioacetamide are dispersed in water and mixed evenly, and then subjected to a hydrothermal treatment to obtain the product.
3. The preparation method according to claim 2, characterized in that: The template agent is polyvinyl pyrrolidone; Alternatively, the chelating agent is salicylic acid.
4. The preparation method according to claim 2, characterized in that: The zinc salt, manganese salt, template agent and chelating agent are calculated as zinc acetate dihydrate, manganese acetate tetrahydrate, PVP and salicylic acid respectively, and the mass ratio of zinc salt, manganese salt, template agent and chelating agent is 0.4-0.6:0.2-0.3:1:0.3-0.
5.
5. The preparation method according to claim 2, characterized in that: The solvent used in the solvothermal method is ethanol; Alternatively, the temperature of the solvothermal method is 160-180°C and the time is 10-12 hours.
6. The preparation method according to claim 2, characterized in that: The calcination temperature is 500-600°C, and the calcination time is 3.5-4.5h; preferably, the calcination heating rate is 1-5°C·min -1 .
7. The preparation method according to claim 2, characterized in that: The temperature of the hydrothermal treatment is 180-190°C and the time is 24-26 hours.
8. The preparation method according to claim 2, characterized in that: The cadmium salt is calculated as cadmium acetate dihydrate, and the mass ratio of the Zn2MnO4 hollow sphere material, the cadmium salt and thioacetamide is 1:1.0-17.5:0.3-5.0, preferably 1:3.70-3.80:1.20-1.
30.
9. Use of the multi-shell composite catalytic material according to claim 1 in photocatalytic water decomposition to produce hydrogen.
10. The use according to claim 9, characterized in that: The multi-shell composite catalytic material is added into a solution containing sodium sulfide and sodium sulfite, mixed evenly, and irradiated with light.